PENANAMAN PENDIDIKAN KARAKTER SEBAGAI PENGUATAN MODERASI BERAGAMA SANTRI DI PANTI ASUHAN MUHAMMADIYAH - Oktafiana, Shinta; Risdiana, Faraniena Yunaeni; Rizaq, Agung Dwi Bahtiar El; Khairi, Ahmad Imam; Rahman, Muhammad Hadiatur; Romadhon, Sahrul; Abdullah, A. Fathikul Amin; Tianah, Itaanis (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
The importance of religious moderation to be instilled in the younger generation, given the growing threat of radicalism and intolerance in society. Radical and intolerant views can cause division, conflict, and national disintegration.. The objective to be achieved from this community service is to identify the cultivation of character education as a strengthening of religious moderation in santri at the Muhammadiyah Pamekasan Orphanage. This community service is expected to provide knowledge and insight into the cultivation of character education as a strengthening of religious moderation in students at the Muhammadiyah Pamekasan Orphanage. The methodology of service on the cultivation of character education as a strengthening of religious moderation is the model in community service using the asset-based community development (ABCD) model by looking at the potential that exists in the Pamekasan Muhammadiyah Orphanage. Participants were 35 male students with ethnic and age diversity. The facilitator advised as a companion in the process of instilling character education based on religious moderation. The result of this service is that the application of educational materials or interventions has a significant positive impact on the character development of respondents with indicators of respect and understanding of others also showing a significant increase, with a high percentage of respondents who are now in the very well developed category.